2019
DOI: 10.1038/s41598-019-43239-x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Basal Nitric Oxide Production Induces Precancerous Mammary Lesions via ERBB2 and TGFβ

Abstract: One third of newly diagnosed breast cancers in the US are early-stage lesions. The etiological understanding and treatment of these lesions have become major clinical challenges. Because breast cancer risk factors are often linked to aberrant nitric oxide (NO) production, we hypothesized that abnormal NO levels might contribute to the formation of early-stage breast lesions. We recently reported that the basal level of NO in the normal breast epithelia plays crucial roles in tissue homeostasis, whereas its red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(47 citation statements)
references
References 159 publications
3
41
0
Order By: Relevance
“…The declined basal NO production is due to reduced bioavailability of the NOS cofactor, BH 4 , under oxidative stress. Consistently, ectopic addition of the BH 4 precursor, sepiapterin, restores basal NO production and inhibits proliferation of breast cancer cells [ 39 ].…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…The declined basal NO production is due to reduced bioavailability of the NOS cofactor, BH 4 , under oxidative stress. Consistently, ectopic addition of the BH 4 precursor, sepiapterin, restores basal NO production and inhibits proliferation of breast cancer cells [ 39 ].…”
Section: Resultsmentioning
confidence: 96%
“…We recently reported that breast epithelial cells produce basal NO when cultivated in the basement membrane. Conversely, the production is impaired in cells undergoing the early-stage breast carcinogenesis, resulting in the upregulation of TGFβ and HER2 [ 37 39 ]. The declined basal NO production is due to reduced bioavailability of the NOS cofactor, BH 4 , under oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the mechanical reverting and the development of the same phenotypically healthy program observed by [ 92 ] was promoted in the case of SNAP. Furthermore, the culture of the breast cancer progression series premalignant AT1, malignant CA1d and DCIS cells, able to form ductal carcinoma in situ , in IrECM gel caused reduced production of NO and nitrite along with reduced levels of the cytosolic SNOC compared to MCF10A cells [ 128 ]. However, the levels of nNOS and eNOS remained high in all cell lines, with a reduction in the levels of iNOS; both nNOS and eNOS share equally in maintaining the basal NO levels in MCF10A cells.…”
Section: Influence Of the Ecm And No On Tumour Angiogenesis In Differmentioning
confidence: 99%